Rough Landscaping For The Strategic Territory Of Valalika Ii. Stage - Areas 4 And 10 [Tender documents : T489613380] (MENA Report, 2023)
Contract notice: rough landscaping for the strategic territory of valalika ii. stage - areas 4 and 10 The purpose and goal of rough landscaping is to prepare the area of interest so that the future construction site is ready for the investor to build a production plant, in terms of the defined requirements (bearing capacity on the surface and in the subsoil, permissible settlement, plan surface, etc.) for the final level 0.000.Recapitulation marginal conditions for the processing of htu transport of unusable topsoil and excess unsuitable material is assumed up to a maximum distance of 30 km, compaction of embankments must be carried out in layers with a thickness of max. 250 - 300 mm with the achievement of the following parameters of the final level of the static modulus of deformation, including the ratio between two load cycles of the static load test: edef.2 60 mpa, edef,2/edef,1 2.5, for areas under buildings.Edef,2 45 mpa edef.2/edef,1 2.5, for areas under roads, parking lots, container areas, railway tracks, etc.; the filling material must be of the nature of gravelly soil fraction 0 63 mm, with the proportion of grains with a diameter d < 0.063 mm less than 5%, characterized according to stn 72 1001 as soil class g3/g-f, on areas under buildings where there is no gravel layer, a 300 mm thick gravel layer will be created, which will serve as a suitable working surface in case of rain for the purpose of minimizing downtime. the thickness of the embankment of gravelly soil (in the embankment as well as in the place of subsoil replacement) will respect the class of the soil in the subsoil as well as its bearing capacity. max. the floor plan dimension of the flat foundations is 3.0 m x 3.0 m. within the framework of the execution of the subject of the contract, the successful applicant will perform in particular: removal and horizontal relocation of grasses, reeds and bushes; removal, relocation, storage, removal and spreading of topsoil; excavations, digging of pits, relocation of the trench , depositing rubble in landfills; subsoil compaction, depositing rubble in an embankment of cohesive rock with a compaction rate of 96 to 100% according to the proctor-standard for areas under buildings, roadways, parking lots, container areas, railway tracks, etc.; subsoil compaction, depositing rubble in embankment of cohesive rock with a compaction rate of 96 to 100% according to the proctor standard for other areas (areas intended for future construction and the plain under green areas); implementation of a drainage system (gutters, gutters, drainage system) establishment of temporary construction site roads for the implementation of works on the areas ht ii and their subsequent liquidation, insulation against water and moisture, preparation of project documentation in the scope of: - project of temporary traffic marking - control and test plan - project of construction organization (pov) - documentation for the implementation of the construction Major organization : VALALIKY INDUSTRIAL PARK, S. R. O. Address : Mlynsk nivy 44/a Country :Slovakia Email : peter.bartos@r-p.sk Url : www.valaliky.eu Tender notice number : 343290-2023 Notice type : T489613380.html © 2022 Al Bawaba (Albawaba.com) Provided by SyndiGate Media Inc. (Syndigate.info).